Mucormycosis and COVID-19 an epidemic in a pandemic? - Banerjee, Indrajit; Robinson, Jared; Asim, Mohammad; Sathian, Brijesh; Banerjee, Indraneel (Nepal Journal of Epidemiology, 2021)
Mucormycosis and aspergillosis are rare, invasive and life-threatening infections primarily caused by Rhizopus arrhizus and Aspergillus fumigatus with higher case fatality rates (>50%), respectively. Invasive Aspergillosis and Mucormycosis have been established and recognized as complications of the SARS-CoV-2 infection. Such cases have been intimately linked and related to prior corticosteroid therapy. With the new highly infectious Delta strain (B.1.617.2 and B.1.617.2.1 or AY.1) of the coronavirus which is running rampant throughout India causing unprecedented death tolls, a new crisis is evolving. Invasive “black fungus” (Mucormycosis) is creating an epidemic within a global pandemic. The unique socio-economic, genetic and health status of Indian population culminates into a melting pot which sustains the viable triad for the “black fungus” infection to gain a stronghold. Diabetes mellitus, immunosuppression and the current COVID-19 global pandemic with its massive surges in the country have produced the “perfect storm.” Ophthalmologist across India have reported a surge in invasive Mucormycosis cases with a rise in orbital compartment syndrome often calling for radical procedures such as enucleation surgeries. The “black fungus” pandemic and invasive Mucormycosis resulted in the sinister secondary infections and complications are closely linked with the COVID-19 infection in India. It is therefore of the upmost importance that neighbouring countries particularly Nepal and other Asiatic nations take great cognizance of this indolent “black fungus killer” and ensure new screening and testing protocols for early identification to ensure effective management.